Math, asked by laisonantony590, 5 months ago

plz find the answer urgent

will mark brilliant​

Attachments:

Answers

Answered by Rajarsee
1

Answer:

(4x²y)+(-3xy²)+(-5xy²)+(5x²y)

=4x²y-3xy²-5xy²+5x²y

=9x²y-8xy²

Hope this solved your problem..Mark me as Brainliest.

Answered by rosy1412
0

Step-by-step explanation:

If we add 2x  

2

y,−4x  

2

y,6x  

2

y,−5x  

2

y then we get,

2x  

2

y−4x  

2

y+6x  

2

y−5x  

2

y

=−2x  

2

y+6x  

2

y−5x  

2

y

=4x  

2

y−5x  

2

y

=−x  

2

y

Similar questions